Enhanced composite performance: Evaluating silane treatment on Cordia dichotoma Fibers - Kuncoro Diharjo; Andoko Andoko; Johny W Soedarsono; Femiana Gapsari; Sanjay Mavinkere Rangappa; Suchart Siengchin (Results in Engineering)
The increasing demand for sustainable materials has driven interest in natural fibers like Cordia dichotoma for composite reinforcement. However, their application is limited by weak fiber-matrix adhesion, poor thermal stability, and high moisture absorption. This study investigates the effects of silane treatment on the mechanical and thermal properties of Cordia dichotoma fibers (CF). Fibers treated with 1 % silane achieved a tensile strength of 105.37 MPa, an elongation of 1.53 %, and a modulus of elasticity of 5.14 GPa—representing significant improvements compared to untreated fibers. The thermal stability also increased, with decomposition temperatures rising from 341 °C (untreated) to 355 °C. Excessive silane concentrations negatively affected fiber integrity. This research highlights the potential of silane-treated CF in high-performance composite applications.